Schistosome eggs stimulate reactive oxygen species production to enhance M2 macrophage differentiation and promote hepatic pathology in schistosomiasis. - Yanxiong Yu; Junling Wang; Xiaohong Wang; Pan Gu; Zhigang Lei; Rui Tang; Chuan Wei; Lei Xu; Chun Wang; Ying Chen; Yanan Pu; Xin Qi; et al. (PLoS Neglected Tropical Diseases, 2021)
Schistosomiasis is a neglected tropical disease of public health concern. The most devastating pathology in schistosomiasis japonica and mansoni is mainly attributed to the egg-induced granulomatous response and secondary fibrosis in host liver, which may lead to portal hypertension or even death of the host. Schistosome eggs induce M2 macrophages-rich granulomas and these M2 macrophages play critical roles in the maintenance of granuloma and subsequent fibrosis. Reactive oxygen species (ROS), which are highly produced by stimulated macrophages during infection and necessary for the differentiation of M2 macrophages, are massively distributed around deposited eggs in the liver. However, whether ROS are induced by schistosome eggs to subsequently promote M2 macrophage differentiation, and the possible underlying mechanisms as well, remain to be clarified during S. japonicum infection. Herein, we observed that extensive expression of ROS in the liver of S. japonicum-infected mice. Injection of ROS inhibitor in infected mice resulted in reduced hepatic granulomatous responses and fibrosis. Further investigations revealed that inhibition of ROS production in S. japonicum-infected mice reduces the differentiation of M2, accompanied by increased M1 macrophage differentiation. Finally, we proved that S. japonicum egg antigens (SEA) induce a high level of ROS production via both nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 (NOX2) and mitochondria in macrophages. Our study may help to better understand the mechanism of schistosomiasis japonica-induced hepatic pathology and contribute to the development of potential therapeutic strategies by interfering with ROS production.